PENGARUH HEATER PADA KELEMBABAN DAN SUHU DI DALAM PROOFER TERHADAP PERKEMBANGAN ROTI - Kun Suharno; Catur Pramono; Rachel Chandra Aditama; Fuad Hilmy (Journal of Mechanical Engineering, 2019)
In the process of making bread, proofing is important. In existing UKM, the proofing process still uses boiled water in the pan and then placed under the cupboard. Based on these problems, the author tried to examine the effect of a 100 watt heater on the humidity and temperature in the proofer on the development of bread. This study was conducted by analyzing the development of bread using variations of time 150 minutes, 160 minutes, and 170 minutes. The temperature used is 37 Celcius degree and the humidity is 94%. The volume of the dough is 191.09 cm cubics which is placed in a 40 cm x 60 cm pan and inserted into the proofer. The water used is tubular with fingers 7.5 cm and 15 cm high. A heater with 100 watt of power is placed in the water. The results showed that the effect of 37 Celcius degree on the development of bread with a time variation of 160 minutes got the best results, namely the dough can expand to 535.05 cm cubics.